2018
DOI: 10.3390/ijerph15112380
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Surgical Simulation for Yaw Control of the Mandibular Condyle and Its Actual Application to Orthognathic Surgery: A One-Year Follow-Up Study

Abstract: Background: Favourable occlusal interdigitation and an optimized position of the mandibular condyle after surgery are essential for obtaining favourable results. The position of the condyle is determined during the operation. However, it is difficult to maintain the condyle’s original position post-surgery despite the efforts of the surgeons. Indeed, a degree of rotation of the condyle is unavoidable, since it is difficult to verify whether the condyle is positioned correctly during surgery. Purpose: To maximi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…In the CP group, plates were premade according to the preoperative 3D diagnosis and design ( Figure 2 and Figure 3 ). During OGS in the CP group, condyle positioning was performed using a customized plate and proximal segment positioning device [ 14 ], not the method used in the NCP group.…”
Section: Methodsmentioning
confidence: 99%
“…In the CP group, plates were premade according to the preoperative 3D diagnosis and design ( Figure 2 and Figure 3 ). During OGS in the CP group, condyle positioning was performed using a customized plate and proximal segment positioning device [ 14 ], not the method used in the NCP group.…”
Section: Methodsmentioning
confidence: 99%
“…It has been proven that using a preformed reconstruction plate has many advantages relative to a manually bent plate in operation, such as fractures, tumor resection, orthodontic surgery, and implant surgery. [ 6 , 15 17 ] However, even experienced surgeons face difficulty in placing the preformed plate in the same position as its preoperative design because of unstable bone segments and the lack of effective stabilization after the tumorectomy stage. In this project, a specially designed reconstruction guide template solved the difficulty of placing the preformed titanium plate via determinations during preoperative virtual design.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported a high success rate of mandibular reconstruction with digital surgical techniques, including surgical navigation and 3-dimensional (3D) digital guide technology, [ 4 6 ] which have markedly improved the precision and minimally invasive performance of modern oral and maxillofacial surgery. For instance, using a reconstructed three-dimensional skull model to pre-bend the titanium plate could assist correction of mandibular defects to a certain extent and check the effect of bond repair.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent study, the condyle position was adjusted to establish the optimal relationship between the proximal and distal segments during mandibular virtual surgery. However, there were cases wherein the condyle–fossa relationship after the operation was not similar to that after the virtual surgery [ 19 ].…”
Section: Introductionmentioning
confidence: 99%